2016
DOI: 10.1093/mnras/stw135
|View full text |Cite
|
Sign up to set email alerts
|

The extended Baryon Oscillation Spectroscopic Survey: a cosmological forecast

Abstract: We present a science forecast for the eBOSS survey. Focusing on discrete tracers, we forecast the expected accuracy of the baryonic acoustic oscillation (BAO), the redshift-space distortion (RSD) measurements, the f NL parameter quantifying the primordial non-Gaussianity, the dark energy and modified gravity parameters. We also use the line-of-sight clustering in the Ly-α forest to constrain the total neutrino mass. We find that eBOSS LRGs, ELGs and Clustering Quasars (CQs) can achieve a precision of 1%, 2.2% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 70 publications
5
141
1
Order By: Relevance
“…We also look forward to larger data sets with eBOSS (Zhao et al 2016), the Subaru Prime Focus Spectrograph (PFS; Takada et al 2014), DESI (Levi et al 2013), Euclid (Laureijs 2009;Laureijs et al 2011), LSST (Tyson 2002), and WFIRST (Spergel et al 2013a,b) that can be matched up to deeper imaging.…”
Section: Discussionmentioning
confidence: 99%
“…We also look forward to larger data sets with eBOSS (Zhao et al 2016), the Subaru Prime Focus Spectrograph (PFS; Takada et al 2014), DESI (Levi et al 2013), Euclid (Laureijs 2009;Laureijs et al 2011), LSST (Tyson 2002), and WFIRST (Spergel et al 2013a,b) that can be matched up to deeper imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Forecasts in Zhao et al (2016) predict 1% precision on isotropic BAO with 7000 deg 2 for the final eBOSS LRG sample (when combined with the high-redshift tail of CMASS). For the current footprint with A eff =1844 deg 2 , the forecast scales to a 1.95% BAO measurement assuming that the error is Figure 13.…”
Section: Comparison With Previous Bao Measurementsmentioning
confidence: 99%
“…The main goal of eBOSS is to measure BAO distances at 1.6% precision level using 500k clustering quasars, 1.4% using Lyα forests, 2.2% with 200k emission line galaxies (ELGs), and 1% from 300k luminous red galaxies (LRGs). With these galaxy and quasar samples, eBOSS will produce the best measurements of the growth rate of structures from RSD: 2.8%, 3.3%, and 2.5% precision, respectively, from quasars, ELGs, and LRGs (Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly in this model space the range of variation in observed quantities is quite small. In this figure, we also include projections for eBOSS (Dawson et al 2016;Zhao et al 2016) as open symbols. Simple parameterizations of the equation of state of dark energy w allow us to study aspects of the observed acceleration without explicit assumptions about its physical cause.…”
Section: Analysis Of Individual Modelsmentioning
confidence: 99%